La «nova cançó» i l'escriptura lírica - Meseguer, Lluís (Caplletra. Revista Internacional de Filologia, 1997)
The Nova Cançó has not only been an important linguistic and civil phenomenon in Catalan life in the latest decades. It has also been a literary phenomenon that deserves to be analysed, taking into account both the lyrics of the important authors and the great variety and quantity of poems that, with music, became songs. The article studies this artistic production.